The insulin-like growth factor system is modulated by exercise in breast cancer survivors: a systematic review and metaanalysis (2016)
Background: Insulin-like growth factors (IGF´s) play a crucial role in controlling cancer cell proliferation, differentiation and apoptosis. Exercise has been postulated as an effective intervention in improving cancerrelated outcomes and survival, although its effects on IGF´s are not well understood. This meta-analysis aimed to determine the effects of exercise in modulating IGF´s system in breast cancer survivors. Methods: Databases of PuMed, EMBASE, Cochrane Central Register of Controlled Trials, EMBASE, ClinicalTrials. gov, SPORTDiscus, LILACS and Scopus were systematically searched up to November 2014. Effect estimates were calculated through a random-effects model of meta-analysis according to the DerSimonian and Laird method. Heterogeneity was evaluated with the I 2 test. Risk of bias and methodological quality were evaluated using the PEDro score. Results: Five randomized controlled trials (n = 235) were included. Most women were post-menopausal. Highquality and low risk of bias were found (mean PEDro score = 6.2 ± 1). Exercise resulted in significant improvements on IGF-I, IGF-II, IGFBP-I, IGFBP-3, Insulin and Insulin resistance (P 0.05). Non-significant differences were found for Glucose. Aerobic exercise improved IGF-I, IGFBP-3 and Insulin. No evidence of publication bias was detected by Egger´s test (p = 0.12). Conclusions: Exercise improved IGF´s in breast cancer survivors. These findings provide novel insight regarding the molecular effects of exercise on tumoral microenvironment, apoptosis and survival in breast cancer survivors.